2018
DOI: 10.1161/jaha.117.007546
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling in Acute ST‐Segment–Elevation Myocardial Infarction Identifies Succinate as an Early Marker of Human Ischemia–Reperfusion Injury

Abstract: BackgroundIschemia–reperfusion injury following ST‐segment–elevation myocardial infarction (STEMI) is a leading determinant of clinical outcome. In experimental models of myocardial ischemia, succinate accumulation leading to mitochondrial dysfunction is a major cause of ischemia–reperfusion injury; however, the potential importance and specificity of myocardial succinate accumulation in human STEMI is unknown. We sought to identify the metabolites released from the heart in patients undergoing primary percuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 15 publications
2
71
0
Order By: Relevance
“…Regular exercise and chronic hypoxia are natural stimuli that produce sustainable cardioprotection against ischemia reperfusion . Consistent with the important role of succinate in muscle metabolism and fiber remodeling we showed, succinate is elevated in the blood in response to exercise and accumulated rapidly in hypoxic/ischemic tissues , suggesting a potential role of succinate in exercise/hypoxia‐mediated cardioprotection. Succinate may act as a paracrine or endocrine signaling molecules via SUCNR1 to regulate local cellular metabolism , or increase tissue blood supply through the renin‐angiotensin system, thereby alleviating tissue hypoxia and hypoxia adaptation of metabolism in the environment .…”
Section: Discussionsupporting
confidence: 83%
“…Regular exercise and chronic hypoxia are natural stimuli that produce sustainable cardioprotection against ischemia reperfusion . Consistent with the important role of succinate in muscle metabolism and fiber remodeling we showed, succinate is elevated in the blood in response to exercise and accumulated rapidly in hypoxic/ischemic tissues , suggesting a potential role of succinate in exercise/hypoxia‐mediated cardioprotection. Succinate may act as a paracrine or endocrine signaling molecules via SUCNR1 to regulate local cellular metabolism , or increase tissue blood supply through the renin‐angiotensin system, thereby alleviating tissue hypoxia and hypoxia adaptation of metabolism in the environment .…”
Section: Discussionsupporting
confidence: 83%
“…Plasma succinate may participate in a similar cycle, perhaps with glutamine/glutamate as metabolites returning to hypoxic tissue. In agreement with this, a recent study on plasma metabolites in the coronary sinus of ischemic human myocardium identified elevated succinate and lower glutamate ( Kohlhauer et al, 2018 ).…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore addition of malonate upon reperfusion is also protective 130,131 . In addition, some succinate is released from the ischemic tissue into the circulation upon reperfusion 132 and can activate the pro-inflammatory succinate receptor (SUNCR1) which is expressed in immune cells, thereby stimulating inflammatory damage [133][134][135] . These findings suggest that inhibitors of succinate accumulation during ischemia, and its oxidation and release during reperfusion are promising therapeutic agents 136 .…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 99%